Information Resources for Online Learning: An Instant Trust Perspective - See-To, Eric W. K. (Proceedings of the International Conference on Networked Learning, 2010)
The learning environment is fast changing in the era of digital world. The new era of online learning will be student-centric, relying heavily on online learning resources. The increasing pervasiveness of online learning, together with the rise of student-centric way of learning in the online era, highlights the need to understand how students interact with the resources available online. In this paper, we focus on one particular element - how users place trust on online learning resources. Research suggested that online learners place trust almost instantly on online information resources, without much evaluation of the sources, and trust the Internet too much by default, treating it the same as a formal library. Given the need for suitable approaches to understand the formation of online user trust on learning resources, this paper aims at taking a first step by providing an overview of relevant literature for analyzing the online trust formation process. We propose that the e-commerce trust literature is a promising starting point. In the e-commerce context, consumer trust is a big obstacle - it is so difficult to engender trust. In the online learning context, we are facing a somewhat reversed problem: users are placing trust on online information resources so quickly- instantly, and we need to understand the process. We find that a dynamic dimension of trust formation is missing in the current literature. The dynamic, instant dimension of trust is not well understood. Given the special instant nature of online trust, we propose that there is a niche in the extant literature for a dynamic approach of investigating the formation of trust by users on online learning resources.